Penerapan Penyaluran Dana Zakat Pada BAZNAS Kabupaten Padang Lawas Utara - Harahap, Monica; Lubis, Delima Sari; Lubis, Rini Hayati (Journal of Islamic Social Finance Management, 2024)
AbstractThe presence of BAZNAS North Padang Lawas Regency is one of the zakat management bodies in North Padang Lawas Regency which has a consumptive and productive fund distribution program, related to zakat assistance, the assistance provided is chosen collectively by the department. The discussion in this research relates, among other things, to zakat, the legal basis for zakat, the urgency and purpose of zakat, distribution of zakat, the function of zakat management, and utilization of zakat, as well as effectiveness. This type of research is qualitative research as a form of field research, namely research activities used to make observations and obtain data in the field, using data collection techniques in the form of observation, interviews and documentation. The results of the research explain that the implementation of the distribution of zakat funds implemented by Baznas in North Padang Lawas Regency basically includes several things, starting from collection, distribution, utilization to evaluation which refers to the Shari'a and the Law. The research results show that the distribution of Zakat funds has not been distributed effectively, where several problems include problems with BAZNAS, human resources and the government. Where BAZNAS in selecting mustahiq recipients of zakat assistance has not been effective and there is a lack of socialization. Meanwhile, human resources still lack knowledge in managing business capital zakat assistance, due to a lack of socialization and supervision from both BAZNAS and the government.Keywords : Implementation, Distribution, Zakat FundAbstrakKehadiran BAZNAS Kabupaten Padang Lawas Utara merupakan salah satu badan pengelola zakat di Kabupaten Padang Lawas Utara yang memiliki program penyaluran dana secara konsumtif dan produktif, terkait mengenai bantuan zakat, bantuan yang diberikan di pilih secara kolektif oleh dinas. Pembahasan dalam penelitian ini antara lain berkaitan dengan zakat, landasan hukum zakat, urgensi dan tujuan zakat, penyaluran zakat, fungsi pengelolaan zakat, dan pendayagunaan zakat, serta efektivitas. Jenis penelitian ini adalah penelitian kualitatif sebagai bentuk penelitian lapangan, yaitu kegiatan penelitian yang digunakan untuk mengadakan pengamatan dan memperoleh data di lapangan, dengan menggunakan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menjelaskan bahwa Implementasi penyaluran Dana zakat diterapkan Baznas Kabupaten Padang Lawas Utara pada dasarnya meliputi beberapa hal yaitu mulai dari pengumpulan pendistribusian pendayagunaan hingga evaluasi yang merujuk kepada syariat dan Undang-Undang. Hasil penelitian Menunjukkan bahwa penyaluran Dana Zakat belum disalurkan secara efektiv, dimana beberapa masalah diantaranya masalah BAZNAS, SDM, dan Pemerintah. Dimana BAZNAS dalam memilih mustahiq penerima bantuan zakat belum efektiv dan kurangnya sosialisasi. Sedangkan SDM masih sangat kurang pengetahuan dalam mengelola bantuan zakat modal usaha, karena kurangnya sosialisasi dan pengawasan baik dari BAZNAS maupun pemerintah.Kata Kunci :  Implementasi, Penyaluran, Dana Zakat